Prognostic value of long non-coding RNA BLACAT1 in patients with papillary thyroid carcinoma - Liao, Denghui (Cancer Cell Int, 2018)
BACKGROUND: Long noncoding RNAs (lncRNAs) have been reported to have potential diagnostic and prognostic values for numerous cancers. However, the plasma expression of lncRNA BLACAT1 and its clinical value in patients with papillary thyroid cancer (PTC) remain unknown. METHODS: The expression profile of BLACAT1 in 87 PTC patients (case group) and 36 patients with nodular goiter (control group) were investigated by qRT-PCR. The Kaplan–Meier method was used for RFS curves, and the univariate survival differences were analyzed by the log-rank test. RESULTS: BLACAT1 expression was downregulated in the plasma of case group compared with control group (P = 0.003). We also found that low plasma BLACAT1 expression was correlated with lymph node metastasis (LNM) (P < 0.001). Multivariate analysis showed that BLACAT1 was an independent risk factor for lymph node metastasis and gender (P < 0.05). The area under the ROC curve for BLACAT1 was 0.825 in LNM prediction (P < 0.001). CONCLUSION: The present study demonstrated that BLACAT1 could act as a possible suppressor gene in PTC and may serve as a potential biomarker for prognosis prediction of PTC.